Hydration status and urine acidity of T team FC players / Muhammad Syafiq Mohd Jaafar - Mohd Jaafar, Muhammad Syafiq (Faculty of Sport Science and Recreation, 2016)
The aim of this study was to investigate uSG, uPH and urine color on T Team FC players during Malaysian Cup 2015 against Felda United FC. There were eighteen (N=18) players participated on this study. Thus, uSG, uPH and color urination were measured before and after match in this study. (Mean ± SO) on pre match in uSG (1.016 ± .008) and post match was (1.024 ± .007) and for uPH on pre match was (6.694 ± .519) and post match was (6.278 ± .492). The result demonstrated significant differences in uSG and uPH. Players experienced dehydration after the match against Felda United FC. Despite by having euhydration before the game, result of uSG showed players experienced dehydrate based on the statistic total of 1.035 in USG reading. Urine PH level shown of urine acidity increases as well. In conclusion, it is recommended for players to consume water based on recommended from ACSM, (1996) whereby about one hundred and fifty (150ml) to three hundred (300ml) requires every twenty (20) to thirty (30) minutes during games. This is to keep the body hydrated.